THE IMPORTANCE OF EARLY MEDIEVAL MIYONKOL VALLEY – ISHTIKHAN IN SOGD CONFEDERATION AND PECULIARITIES OF RULING - Abdirazakovich, Khushbakov Hamidulla (International Journal of Psychosocial Rehabilitation, 2020)
In the beginning of the middle ages there was confederation govern in Sogd. Сonfederation was the center of Samarkand, Zarafshan Panch, Maymurg, Ishtikhan, Kabudan, Kushaniya and he controls and monitors areas as Kesh and Naxshab. In this article, based on written sources given the ability to make some judgment about the history of Confederation SogdIshtikhan kingdoms.